4(5x+7)-(3-x)=4

Simple and best practice solution for 4(5x+7)-(3-x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x+7)-(3-x)=4 equation:


Simplifying
4(5x + 7) + -1(3 + -1x) = 4

Reorder the terms:
4(7 + 5x) + -1(3 + -1x) = 4
(7 * 4 + 5x * 4) + -1(3 + -1x) = 4
(28 + 20x) + -1(3 + -1x) = 4
28 + 20x + (3 * -1 + -1x * -1) = 4
28 + 20x + (-3 + 1x) = 4

Reorder the terms:
28 + -3 + 20x + 1x = 4

Combine like terms: 28 + -3 = 25
25 + 20x + 1x = 4

Combine like terms: 20x + 1x = 21x
25 + 21x = 4

Solving
25 + 21x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + -25 + 21x = 4 + -25

Combine like terms: 25 + -25 = 0
0 + 21x = 4 + -25
21x = 4 + -25

Combine like terms: 4 + -25 = -21
21x = -21

Divide each side by '21'.
x = -1

Simplifying
x = -1

See similar equations:

| 2n-n+5=3 | | 10+3-(8)= | | w+2x-3y+5y=-98 | | 30-9(5x+1)=-24 | | 5m=8-23m | | -(4a-8)=2(a+4) | | -30=-5x-15 | | x+4*3=x+18 | | 33%x+6=12 | | -4n+6=-3n+8+4 | | 30-9(5x+1)=24 | | 4x^2-32x+52=0 | | -8+x=11 | | -16x-15=14x-23 | | x=6+-15 | | 7x+8=3x+44 | | -3(2+4p)=2(2p-1) | | 8-11=7k | | -4x-12=36 | | -24-f=-15 | | 4x+7=5x-x-1 | | 2(3-3x)+4=-6(-8+2x)-2 | | 6x^2+7xy+3y^2=144 | | 5log+10=7m | | -8(1-x)=64 | | x-50=16 | | 3b-9-8b=8 | | 2000=-4p^2+60p+1039 | | -4n+6=3n+8+4 | | 3(.9-t)=-5(16+3t) | | 9x-2x+8=3x+38+y | | 5log=-10-7m |

Equations solver categories